Dislocations and particle size governed band gap and ferromagnetic ordering in Ni doped ZnO nanoparticles synthesized via co-precipitation. Issue 17 (1st December 2019) - Chattopadhyay, Saikat; Misra, Kamakhya Prakash; Agarwala, Arunava; Shahee, Aga; Jain, Sukriti; Halder, Nilanjan; Rao, Ashok; Babu, P.D.; Saran, Mukesh; Mukhopadhyay, Anoop Kumar
Abstract: To the best of our knowledge, the present work is the first ever report on how the Ni dopant concentration affects the dislocation density, band gap and most importantly the diamagnetic to ferromagnetic transition in ZnO nanoparticles (NPs), well known for multifunctional applications. For this purpose, undoped and Ni doped (1, 3, 5, and 7 at. wt.%) Wurtzite phase ZnO nanoparticles (NPs in size range 13–34 nm) are synthesized by sol-gel co-precipitation technique. As a function of the dopant concentrations (c), the polycrystalline NPs are characterized by XRD, Williamson-Hall plot, Rietveld refinement, UV–Vis spectroscopy, band-gap evaluation, dislocation density estimation, photoluminescence (PL) spectra, scanning electron microscopy (SEM), vibrating sample magnetometer (VSM) based magnetic moment (M) versus magnetic field (H) measurement, magnetic hysteresis measurement and resistivity (ρ) measurement. The results confirm that the dislocations density ( δ (hkl) ) along the (002) peak of XRD pattern governs the band gap energy (Eg ) estimated from the corresponding Tauc's plot. Further, both δ (hkl) and Eg exhibit interesting empirical dependencies on c. The PL spectra of all the NPs show the blue emission due to Zn interstitials. The SEM based photomicrographs prove the presence of the elongated spherical i.e, elliptical sub-structures forming a chain-like distribution in the microstructures which are sensitive to c. Further, the M-H loop reveal a transition from diamagnetic to ferromagnetic behavior as the presence of Ni in ZnO matrix enhances. A similar behavior is exhibited by ρ. These results are finally summarized in terms of structure-property correlations. The implications of the present materials in terms of possible futuristic applications are also discussed.